Identifying the Transgender Population in the Medicare Program - Proctor, Kimberly (Transgend Health, 2016)
Purpose: To identify and describe the transgender population in the Medicare program using administrative data. Methods: Using a combination of International Classification of Diseases ninth edition (ICD-9) codes relating to transsexualism and gender identity disorder, we analyzed 100% of the 2013 Centers for Medicare & Medicaid Services (CMS) Medicare Fee-For-Service (FFS) “final action” claims from both institutional and noninstitutional providers (∼1 billion claims) to identify individuals who may be transgender Medicare beneficiaries. To confirm, we developed and applied a multistage validation process. Results: Four thousand ninety-eight transgender beneficiaries were identified, of which ∼90% had confirmatory diagnoses, billing codes, or evidence of a hormone prescription. In general, the racial, ethnic, and geographic distribution of the Medicare transgender population tends to reflect the broader Medicare population. However, age, original entitlement status, and disease burden of the transgender population appear substantially different. Conclusions: Using a variety of claims information, ranging from claims history to additional diagnoses, billing modifiers, and hormone prescriptions, we demonstrate that administrative data provide a valuable resource for identifying a lower bound of the Medicare transgender population. In addition, we provide a baseline description of the diversity and disease burden of the population and a framework for future research.